EARLY LIFE COURSE EVENTS AND VOLUNTEERING IN LATE LIFE - Hogerbrugge, M. (Innov Aging, 2017)
Besides highlighting heterogeneity in life courses and the impact of socio-historical time, geographical location, human agency, and linked lives, the life course perspective underlines the significance of [the timing of] transitions and events earlier in the life course in shaping the later life of individuals – a principle also known as path dependency. Employing data from the life history interview and subsequent waves of the English Longitudinal Study of Ageing (ELSA), we test to what extent the experience of negative events earlier in the life course, as well as the timing of ‘normal’ events (e.g., leaving the parental home, marriage, [first] child birth) affect the frequency of, and reasons for volunteering in late life (age 50 and over). Ordered logistic regressions revealed that the frequency of volunteering was positively affected by the experience of negative events in the life course, especially when they were first experienced at a young age. When ‘normal’ events, such as marriage and parenthood, were experienced at ages outside normative social timetables (i.e., too early or too late), the frequency of volunteering in late life was found to be lower. Examining the reasons for volunteering, individuals who had experienced negative events in their life course, or who experienced ‘normal’ events off-time, were found to report socially related motivations for volunteering more often and motivations related to personal development less often. We discuss the relevance of our findings in light of the notion of ‘active ageing’ and related policies.